Health and illness in the community - edited by Ross J. Taylor; Blair H. Smith; Edwin R. van Teijlingen (Oxford University Press, 2003)
This concise multi-disciplinary textbook for medical students takes a practical approach to the subject, integrating the subjects that are being taught within the community. Taking health and normality as a starting point, the book considers the environmental and social factors which influence the health of a community, discussing the nature, distribution and determinants of illness. Students need a solid understanding of medicine in the community encompassing elements of public health, general practice, child health, geriatrics, mental health, psychology and sociology and this book provides the material required. OXFORD CORE TEXTSThe Oxford Core Text series provides concise, yet comprehensive coverage of a range of essential topics in the medical curriculum. Written and tested in concultation with students, each book offers a clear and accessible account of the core material, supported by many case studies, learning aids and clinical examples. All titles include the key information which the reader will need to prepare for successful clinical practice - making these texts ideal for all stages of the medical curriculum and beyond